Extending the scope of the interpersonal psychotherapy model of eating disorders: Integrating the role of 'feeling fat'. (1st November 2021) - Trolio, Vittoria; Mehak, Adrienne; Schell, Sarah E.; Racine, Sarah E.
Abstract: The interpersonal psychotherapy model of eating disorders (IPT-ED) argues that interpersonal problems result in negative affect, and that an inability to cope with this negative affect triggers ED symptoms. Relatedly, it is theorized that 'feeling fat' (i.e., the somatic experience of being overweight not entirely explained by one's body mass) results from shifting negative affect onto one's body, which can then be controlled via ED symptoms. Research has yet to identify why negative affect caused by interpersonal problems may trigger ED symptoms as opposed to other maladaptive behaviours. Integrating 'feeling fat' into the IPT-ED may help to explain this relationship. This study examined whether interpersonal problems positively related to ED symptoms via negative affect and 'feeling fat' in 190 undergraduate women (mean age [SD] = 19.05 [1.23]; mean BMI [SD] = 21.76 [3.17]; 72.8% Caucasian). Using both cross-sectional and longitudinal path analyses, we tested the indirect effects of ostracism and peer victimization on binge eating and restricting via negative affect and 'feeling fat' using serial indirect effects analyses. Cross-sectional path analysis revealed significant indirect effects of ostracism on both binge eating and restricting sequentially via negative affect and 'feeling fat', such that ostracism related to negative affect, which related to 'feeling fat', which was ultimately associated with disordered eating behaviours. Longitudinal path analysis replicated the significant indirect effects of ostracism on binge eating sequentially via negative affect and 'feeling fat'. Results suggest that individuals may displace negative feelings that result from ostracism onto their body, triggering 'feelings of fatness' and prompting ED symptoms. Future research should examine 'feeling fat' within the IPT-ED in a sample of individuals with EDs to determine its clinical utility beyond an undergraduate sample.